Coronagraphic Demonstration Experiment Using Aluminum Mirrors for Space Infrared Astronomical Observations. (4th January 2016) - Oseki, S.; Oyabu, S.; Ishihara, D.; Enya, K.; Haze, K.; Kotani, T.; Kaneda, H.; Nishiyama, M.; Abe, L.; Yamamuro, T.
Abstract: For future space infrared astronomical coronagraphy, we perform experimental studies on the application of aluminum mirrors to a coronagraph. Cooled reflective optics is required for broadband mid-infrared observations in space, while high-precision optics are required for coronagraphy. For the coronagraph instrument originally proposed for the next-generation infrared astronomical satellite project SPICA (SCI: SPICA Coronagraph Instrument), we fabricated and evaluated the optics consisting of high-precision aluminum off-axis mirrors with diamond-turned surfaces, and conducted a coronagraphic demonstration experiment using the optics with a coronagraph mask. We first measured the wave front errors (WFEs) of the aluminum mirrors with a He-Ne Fizeau interferometer to confirm that the power spectral densities of the WFEs satisfy the SCI requirements. Then we integrated the mirrors into an optical system and evaluated the overall performance of the system. As a result, we estimate the total WFE of the optics to be 33 nm (rms), each mirror contributing 10-20 nm (rms) for the central 14 mm area of the optics, and obtain a contrast of 10 -5.4 as a coronagraph in the visible light. At a wavelength of 5 μm, the coronagraphic system is expected to achieve a contrast of ∼10 -7 based on our model calculation with the measured optical performance. Thus our experiment demonstrates that aluminum mirror optics is applicable to a highly WFE-sensitive instrument such as a coronagraph in space.